2021
DOI: 10.1128/msystems.00299-21
|View full text |Cite
|
Sign up to set email alerts
|

AI4AMP: an Antimicrobial Peptide Predictor Using Physicochemical Property-Based Encoding Method and Deep Learning

Abstract: Antimicrobial peptides (AMPs) are innate immune components that have aroused a great deal of interest among drug developers recently, as they may become a substitute for antibiotics. New candidates need to fight antibiotic resistance, while discovering novel AMPs through wet-lab screening approaches is inefficient and expensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…The early study by Fjell et al [ 114 ] used QSAR descriptors and fed them to an artificial neural network that predicted peptide activity against P. aeruginosa , and achieved 94% accuracy in identifying highly active peptides. Since then, many DL methods have been proposed for predicting AMps [ 80 , 89 , 100 , 114 , 115 , 116 , 117 , 118 , 119 ].…”
Section: Amp Prediction By Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The early study by Fjell et al [ 114 ] used QSAR descriptors and fed them to an artificial neural network that predicted peptide activity against P. aeruginosa , and achieved 94% accuracy in identifying highly active peptides. Since then, many DL methods have been proposed for predicting AMps [ 80 , 89 , 100 , 114 , 115 , 116 , 117 , 118 , 119 ].…”
Section: Amp Prediction By Deep Learningmentioning
confidence: 99%
“…Lin et al [ 119 ] proposed AI4AMP trained on sequences encoded with a combined physicochemical property matrix called PC6. The properties, namely hydrophobicity, volume of side chains, polarity, pH at the isoelectric point, pKa, and the net charge index of side chains, were selected from six clusters of properties based on the result of hierarchical clustering.…”
Section: Amp Prediction By Deep Learningmentioning
confidence: 99%
“…The authors concluded that an ideal encoding DL-based model should consider protein features, such as the physicochemical properties of peptides. Good analysis and choice of parameters lead to a better performance of the prediction software, thus reducing the loss of information when encoding peptides for further processing [ 21 ].…”
Section: Presentmentioning
confidence: 99%
“…According to the results, authors ultimately found that the dose of 4.5×10 6 CFU/mice of E. coli infection. Finally, the bacteria were administered to mice at 4.5×10 6 CFU/mice in the experiment.…”
Section: Antimicrobial Peptide Synthesis Mpx (H-inwk-giaamakkll-nh2mentioning
confidence: 99%
“…Antimicrobial peptides are molecules made up of amino acids produced by the body, they are an important part of the body's immune system (Vimberg et al, 2022). Peptides have low molecular weight, broad antibacterial spectrum, and endurance to resistance (Lin et al, 2021). Peptide molecules consist of 12 to 100 amino acids (Sudadech et al, 2021).…”
Section: Introductionmentioning
confidence: 99%